Spectrum of ocular diseases in aftermath of monsoon flood in Nepal - Sahu, Sabin; Bhutia, Tshering Wangchuk; Shrestha, Varun; Malla, Tejsu; Singh, Sanjay Kumar (Journal of Chitwan Medical College, 2019)
Background: Floods are common global natural disasters that occur occasionally in Nepal. Numerous environmental damages and health impacts are known to occur due to direct effect of flooding. There are limited studies reporting the ocular diseases after the event of floods using a large population data. We aimed to present the spectrum of flood-related ocular diseases after monsoon flood in Nepal using a community-based database. Methods: A descriptive, cross sectional study design was used to collect the data from diagnostic screening and treatment camps organized in flood-affected areas between one to three weeks after the monsoon flood in Nepal. The data was analyzed using the excel sheet and the results were presented in frequency and percentage in the frequency distribution tables. Results: The children and elderly constituted majority of patients. Females constituted 54% while males were 46% of the total patients presenting at the camps. The incidence of infective ocular diseases was 23.8% and that of traumatic ocular injuries was 6.2% of total ocular diseases. Acute conjunctivitis was the most common infective ocular disease (21.1%) followed by keratitis (2.7%). Corneal abrasions (1.4%), subconjunctival hemorrhage (1.1%) and lid ecchymosis (0.7%) were common clinical diagnosis following traumatic ocular injury. Conclusions: The infective ocular diseases and traumatic ocular injuries are common flood-related ocular diseases seen within one to three weeks after flood receded. The knowledge of these expected ocular morbidities may help for proper planning and organization of such relief camps. Early diagnosis and treatment of these diseases can reduce the ocular morbidities.